Science inquiry and writing for ELLs: A gateway for building understanding and academic language. (2nd January 2016) - Huerta, Margarita; Spies, Tracy G.
ABSTRACT: Science education is critical to prepare students with the skills they will need in an increasingly technologically driven society. Yet English language learners (ELLs) consistently struggle to stay on par with their native English-speaking peers in the science classroom. We know, however, that early intervention can prevent ELLs' future learning achievement gaps. In addition, providing ELLs the opportunity to engage in science inquiry and writing integrated activities can help build their academic language and conceptual understanding. In this article we illustrate a science inquiry and writing integrated lesson for young ELLs. In doing so, we discuss how a teacher planned, used, and assessed the science and literacy integrated lesson to scaffold her ELLs' academic language and conceptual understanding within the context of national standards